University Educator and Staff Well-being and Common Mental Health Symptoms during the COVID-19 Pandemic in the Philippines - Justin Vianey M. Embalsado; John Ian Wilzon T. Dizon; Airajoy Keynn S. Medina; Lee Vergel S. Estacio; Beatriz C. Balilu; Mary Anne Joseph T. Montoya; Reymond Neal C. Cruz; Cherry Lou M. De Ala; Olga Angelinetta P. Tulabut; Roger S. Mangalus; Abigail B. Gonzales; Jonee O. Miranda; June R. De Leon (Universitas Ahmad Dahlan, 2022)
Educators and staff adapted to work-from-home setup amidst the covid-19 pandemic.Â The transition to full-online classes and services leads to poor mental health. The current study explored the association of educator and staff personal characteristics, well-being, and mental health.Â 326 university employees completed the demographic profile, mental health, and well-being scales. Various hierarchical regression was conducted to determine if personal characteristics and well-being predict common mental health symptoms (depression, anxiety, and stress). Series of multivariate analyses of variance (MANOVA) was conducted to determine the difference between the levels of mental health symptoms according to mental health category, and personal characteristics. The results support the hypothesis with psychological and emotional well-being inversely predicting depression, anxiety, and stress. However, social well-being failed to serve as a significant determinant of common mental health symptoms. MANOVA obtained a significant difference with common mental health symptoms and mental health category and personal characteristics.